2022
DOI: 10.1002/term.3282
|View full text |Cite
|
Sign up to set email alerts
|

Extruded poly (glycerol sebacate) and polyglycolic acid vascular graft forms a neoartery

Abstract: In the ongoing search for the optimal biomaterial for tissue engineered vascular grafts (TEVGs), poly (glycerol sebacate) (PGS) has emerged as a new potential candidate. We have utilized a novel method to create unique, pore‐free, extruded PGS grafts with and without a supportive exterior layer of polyglycolic acid (PGA). The 1 mm diameter by 5 mm length TEVGs were implanted in a rat model of infrarenal abdominal aorta interposition grafting. Three months after implantation, TEVGs comprised of extruded PGS wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…The absence of elastic fibers is a considerable and general disadvantage of biodegradable TEVGs, albeit a recent study reported the successful formation of the internal elastic lamina by the embedding of tropoelastin fibers into the poly(glycerol sebacate), a highly elastic and degradable biomaterial, during electrospinning [ 74 ]. Yet, the enclosure of poly(glycerol sebacate) or fibrin scaffold into the PCL [ 75 , 76 ] or poly(glycolic acid) [ 77 ] sheath efficiently prevented the development of aneurysms, similar to our previous work [ 60 ]. The lack of contractile VSMCs under significant cyclic strain characteristic of the ovine carotid artery was unexpected, as this is a major stimulus of such molecular specification [ 78 , 79 , 80 ].…”
Section: Discussionsupporting
confidence: 61%
“…The absence of elastic fibers is a considerable and general disadvantage of biodegradable TEVGs, albeit a recent study reported the successful formation of the internal elastic lamina by the embedding of tropoelastin fibers into the poly(glycerol sebacate), a highly elastic and degradable biomaterial, during electrospinning [ 74 ]. Yet, the enclosure of poly(glycerol sebacate) or fibrin scaffold into the PCL [ 75 , 76 ] or poly(glycolic acid) [ 77 ] sheath efficiently prevented the development of aneurysms, similar to our previous work [ 60 ]. The lack of contractile VSMCs under significant cyclic strain characteristic of the ovine carotid artery was unexpected, as this is a major stimulus of such molecular specification [ 78 , 79 , 80 ].…”
Section: Discussionsupporting
confidence: 61%
“… 53 For the extrusion of PGS scaffolds, granulated and pulverized PGS particles can be mixed with a PGS resin, and extruded into a tubular scaffold with a desired diameter followed by heat curing (Figure 2C). 56 …”
Section: Pgs‐based Vascular Grafts For Functional Neoartery Regenerationmentioning
confidence: 99%
“…The incorporation of a sheath layer is the most common method used to address graft dilation. Materials that have strong mechanical properties are usually selected as sheath components including electrospun PCL 46,47,49,50,52,55,61,66,67 and braided PGA, 56 the use of which increases both the suture retention and tensile strength properties of grafts compared to PGSonly grafts.…”
Section: Preventing Dilationmentioning
confidence: 99%
See 1 more Smart Citation
“…The major focus of PGS-inspired polymers is the development of scaffold material for biological tissue engineering ( Wang et al, 2002 ; Gao et al, 2006 ; Gao et al, 2007 ; Jeong and Hollister, 2010 ; Kemppainen and Hollister, 2010 ; Masoumi et al, 2013 ; Khosravi et al, 2016 ; Ma et al, 2016 ; Zhang et al, 2016 ; Nadim et al, 2017 ; Hsu et al, 2018 ; Wu W et al, 2019 ; Hu et al, 2019 ; Jiang et al, 2019 ; Xiao et al, 2019 ; Abudula et al, 2020 ; Fu et al, 2020a ; Apsite et al, 2020 ; Fu et al, 2020b ; Sencadas et al, 2020b ; Jafari et al, 2020 ; Keirouz et al, 2020 ; Liang et al, 2020 ; Martín-Pat et al, 2020 ; Pashneh-Tala et al, 2020 ; Xuan et al, 2020 ; Abazari et al, 2021 ; Behtaj et al, 2021a ; Piszko et al, 2021a ; Liu et al, 2021 ; Rastegar et al, 2021 ; Ângelo et al, 2021 ; Chen et al, 2022 ; Fukunishi et al, 2022 ; Saudi et al, 2022 ), although many other purposes have been identified for these materials. PGS-based materials have been investigated as drug delivery systems ( Sun et al, 2009 ; Sun et al, 2013 ; Yang et al, 2017 ; Ayati Najafabadi et al, 2018 ; Desai et al, 2018 ; Oklu et al, 2018 ; Zhu et al, 2018 ; Rezk et al, 2020 ; Zanjanizadeh Ezazi et al, 2020 ; Sivanesan et al, 2021 ; Torabi et al, 2021 ; Heydari et al, 2022 ; Mehta et al, 2022 ), adhesives ( Mahdavi et al, 2008 ; Tevlek et al, 2017 ; Azerêdo et al, 2022 ), sealants ( Chen et al, 2011 ), coatings ( Kim et al, 2014 ; Lin et al, 2015 ; Ji...…”
Section: Introduction Of Poly (Glycerol Sebacate) (Pgs)mentioning
confidence: 99%